Eksplorasi Etnomatematika pada Pola Gerak Tari Woleka di Gollu Togo Wewewa Barat (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to explore the concept of ethnomathematics found in the movement patterns of the Woleka dance in Gollu Togo, West Wewewa. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The interview subject in this study was the adat leader (rato adat). This study also used data analysis techniques that include data reduction, data presentation, and drawing conclusions. The results show that the Woleka dance has systematic and repetitive movement patterns that reflect mathematical concepts such as symmetry, repeating patterns, and geometric transformations. In addition, cultural artifacts present in the Wewewa community also demonstrate the application of planar and spatial geometric concepts. This research is expected to contribute to culturally based mathematics teaching and to increase appreciation for local cultural richness